Penerapan SAK EMKM Pada Usaha Mochi “AO Daifuku” - Yuliati, Anis; Panggabean, Nilam Riana (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
This research has the main objective to conduct an in-depth analysis related to the application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) to the Ao Daifuku mochi business, which is one of the Student Activity Units (UKM) engaged in the culinary field. The approach used in this research is a qualitative descriptive approach, focusing on understanding and evaluating the extent to which SAK EMKM is applied in Ao Daifuku's financial practices. The object of this research mainly includes an analysis of the financial statements, including the profit and loss and balance sheet of Ao Daifuku's business over a three-month period. The research aims to reveal in detail the process of preparing financial statements and the extent to which Ao Daifuku's financial practices conform to the guidelines set by SAK EMKM. The results show that, although Ao Daifuku has made efforts in recording information on business income and expenses for three months, the preparation of their financial statements still does not fully comply with the EMKM Financial Accounting Standards. This limitation in financial practices can be identified as the main obstacle faced by Ao Daifuku. Thus, this study not only provides an overview of the implementation of SAK EMKM at Ao Daifuku, but also identifies potential remedial measures that can be taken to improve the quality of financial reporting and achieve full conformity with the standard.